Evaluating the feasibility, sensitivity, and specificity of next-generation molecular methods for pleural infection diagnosis - Peter T. Bell; Timothy Baird; John Goddard; Olusola S. Olagoke; Andrew Burke; Shradha Subedi; Tiana R. Davey; James Anderson; Derek S. Sarovich; Erin P. Price (Microbiology Spectrum)
ABSTRACT Pleural infections are common and associated with substantial healthcare costs, morbidity, and mortality. Accurate diagnosis remains challenging due to low culture positivity rates, frequent polymicrobial involvement, and non-specific diagnostic biomarkers. Here, we undertook a prospective study examining the feasibility and performance of molecular methods for diagnosing suspected pleural infection. We prospectively characterized 26 consecutive clinically suspected pleural infections, and 10 consecutive patients with suspected non-infective pleural effusions, using shotgun metagenomics, bacterial metataxonomics, quantitative PCR, and conventional culture. Molecular methods exhibited excellent diagnostic performance, with each method identifying 54% (14 out of 26) positive cases among the pleural infection cohort, versus 38% (10 out of 26) with culture. Metagenomics and bacterial metataxonomics unveiled complex polymicrobial infections that were not captured by culture. Dominant microbes included streptococci (Streptococcus intermedius, Streptococcus pyogenes, and Streptococcus mitis), Prevotella spp. (Prevotella oris and Prevotella pleuritidis), staphylococci (S. aureus and S. saprophyticus), and Klebsiella pneumoniae. However, we encountered challenges that complicated pleural infection interpretation, including: (i) uncertainties regarding microbial pathogenicity and the impact of prior antibiotic therapy on diagnostic performance; (ii) lack of a clinical diagnostic gold-standard for molecular performance comparisons; (iii) potential microbial contamination during specimen collection or processing; and (iv) difficulties distinguishing background microbial noise from true microbial signal in low-biomass specimens. This pilot study demonstrates the potential utility and value of molecular methods in diagnosing pleural infection and highlights key concepts and challenges that should be addressed when designing larger prospective trials.IMPORTANCEConfident pleural infection diagnosis is often challenging due to low culture positivity rates, frequent polymicrobial involvement, and non-specific diagnostic biomarkers. Limitations of conventional diagnostic tests result in prolonged and inappropriately broad-spectrum antimicrobial use, encouraging antimicrobial resistance and leading to avoidable adverse effects. Here, we demonstrate the feasibility, utility, and challenges associated with the use of culture-independent molecular techniques for accurate pleural infection diagnosis in a real-world clinical setting. These data will help to inform the design of larger prospective clinical trials and identify potential obstacles to be overcome before next-generation sequencing technologies can be integrated into routine clinical practice.